Penggunaan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas 3 Mata Pelajaran Fikih Madrasah Ibtidaiyah Darul Ulum Lamongan - Nashihatin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
ducation is a conscious effort made by families, communities and governments through guidance activities, outdoor teaching and exercises that take place in school or outside of school. The effort is carried out in the form of learning where educators serve learners in conducting learning activities and educators assess or measure the success rate of learning with prescribed procedures. The type of research conducted is Classroom Action Research. The formulation of the problem in this study is how the Discovery Learning learning model can improve students' learning outcomes in the subjects of Fikih plural prayer material qasar class III at MI Darul Ulum Lamongan. The results of research using the Discovery Learning model can improve student learning outcomes, especially Fiqh subjects. This was evident in pre-learning with an average score of 62.8 then increased with an average score of 67.9. And in cycle II it increases to 96.85. While the completion of student learning outcomes in pre-cycle is 35%, in the cycle, I am 55% and in cycle II to 70%